2018
DOI: 10.1017/s0954579418000743
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal trajectories of depressive symptoms predict family risk and children's emotional and behavioral problems after the birth of a sibling

Abstract: The current study examined trajectories of maternal and paternal depression in the year following the birth of an infant sibling, and relations with family risk factors and firstborn children's internalizing and externalizing behavior problems. Latent class growth analysis was conducted on 231 families in a longitudinal investigation (prebirth and 1, 4, 8, and 12 months postbirth) and revealed four classes of families: both mother and father low in depressive symptoms (40.7%); mother high–father low (25.1%); f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…Another limitation of the study was that we evaluated parental PND longitudinally, but no specific analyses were run to identify the trajectories of symptomatology, as suggested by recent literature ( 30 , 38 , 40 , 47 ). Also, in our study we did not investigate anxious symptoms, which are known to occur often in comorbidity with depression and may represent the difficulties in parental adjustment after a preterm birth ( 67 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the study was that we evaluated parental PND longitudinally, but no specific analyses were run to identify the trajectories of symptomatology, as suggested by recent literature ( 30 , 38 , 40 , 47 ). Also, in our study we did not investigate anxious symptoms, which are known to occur often in comorbidity with depression and may represent the difficulties in parental adjustment after a preterm birth ( 67 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another methodological issue regards the research design. Indeed, many studies on PND usually have a cross-sectional design, assessing mothers and fathers in one step; to our knowledge, only a few studies investigated the evolution or the trajectories of maternal and paternal PND until 6 or 12 months postpartum ( 30 , 37 , 38 , 40 , 42 , 46 , 47 ). This lack is particularly evident in literature on preterm parents, where only two studies investigated parental PND longitudinally ( 15 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, future studies should analyse the characteristics of boys that may help to explain their increased vulnerability. Considering previous research that showed the effect of fathers’ depression on child developmental outcomes (Volling, Yu, Gonzalez, Tengelitsch, & Stevenson, 2019), future studies should also analyse the effect of fathers’ depression symptoms, specifically during the postpartum period, on infant sleep problems.…”
Section: Discussionmentioning
confidence: 99%
“…Parental stress and depressive symptoms have negative consequences for the partners' relationship satisfaction (Baldoni et al, 2020;Garthus-Niegel et al, 2018 ) and at the same time reduce parental involvement and adequate co-parenting (Bronte-Tinkew et al, 2009;Korja et al, 2008). Several studies have even shown that maternal and paternal stress and depression during pregnancy predict children's mental health problems in the long term, as indicated by an increased risk for internalizing distress and externalizing behaviours (MacKinnon et al, 2018;Tirumalaraju et al, 2020;Van Batenburg-Eddes et al, 2013;Volling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%